# Singular

#### D.6.3.6 internalfunctions

Procedure from library `classify.lib` (see classify_lib).

Usage:
internalfunctions();

Return:
nothing, display names of internal procedures of classify.lib

Example:
 ```LIB "classify.lib"; internalfunctions(); ==> Internal functions for the classification using Arnold's method, ==> the function numbers correspond to numbers in Arnold's classifier: ==> Klassifiziere(poly f); //determine the type of the singularity f ==> Funktion1bis (poly f, list cstn) ==> Funktion3 (poly f, list cstn) ==> Funktion6 (poly f, list cstn) ==> Funktion13 (poly f, list cstn) ==> Funktion17 (poly f, list cstn) ==> Funktion25 (poly f, list cstn) ==> Funktion40 (poly f, list cstn, int k) ==> Funktion47 (poly f, list cstn) ==> Funktion50 (poly f, list cstn) ==> Funktion58 (poly fin, list cstn) ==> Funktion59 (poly f, list cstn) ==> Funktion66 (poly f, list cstn) ==> Funktion82 (poly f, list cstn) ==> Funktion83 (poly f, list cstn) ==> Funktion91 (poly f, list cstn, int k) ==> Funktion92 (poly f, list cstn, int k) ==> Funktion93 (poly f, list cstn, int k) ==> Funktion94 (poly f, list cstn, int k) ==> Funktion95 (poly f, list cstn, int k) ==> Funktion96 (poly f, list cstn, int k) ==> Funktion97 (poly f, list cstn) ==> Isomorphie_s82_x (poly f, poly fk, int k) ==> Isomorphie_s82_z (poly f, poly fk, int k) ==> Isomorphie_s17 (poly f, poly fk, int k, int ct) ==> printresult (string f,string typ,int Mu,int m,int corank,int K) ==> ==> Internal functions for the classifcation by invariants: ==> Cubic (poly f) ==> parity (int e) //return the parity of e ==> HKclass (intvec i) ==> HKclass3( intvec i, string SG_Typ, int cnt) ==> HKclass3_teil_1 (intvec i, string SG_Typ, int cnt) ==> HKclass5 (intvec i, string SG_Typ, int cnt) ==> HKclass5_teil_1 (intvec i, string SG_Typ, int cnt) ==> HKclass5_teil_2 (intvec i, string SG_Typ, int cnt) ==> HKclass7 (intvec i, string SG_Typ, int cnt) ==> HKclass7_teil_1 (intvec i, string SG_Typ, int cnt) ==> ==> Internal functions for the Morse-splitting lemma: ==> Morse(poly fi, int K, int corank) //splitting lemma itself ==> Coeffs (list #) ==> Coeff ==> ==> Internal functions providing tools: ==> ReOrder(poly f) ==> Singularitaet(string typ,int k,int r,int s,poly a,poly b,poly c,poly d) ==> RandomPolyK ==> Faktorisiere(poly f, poly g, int p, int k) compute g = (ax+by^k)^p ==> Teile(poly f, poly g); //divides f by g ==> GetRf(poly f, int n); ==> Show(poly f); ==> checkring(); ==> DecodeNormalFormString(string s); ==> Setring(int n, string ringname); ==> ```